2006
DOI: 10.1177/135965350601100414
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-Binding Lectin in Susceptibility and Progression of HIV-1 Infection in Children

Abstract: Background Mannose-binding lectin (MBL; encoded by MBL-2) is a circulating pattern-recognition molecule that recognizes microbial carbohydrate motifs, leading to complement activation and cell lysis. Mutations in the MBL-2 promoter and of the MBL-2 gene exon 1 result in reduced protein levels and increased susceptibility to infection. We have investigated the effect of MBL-2 polymorphisms on susceptibility and progression of HIV-1 infection in children. Patients and methods One-hundred and twenty-eight childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…MBL‐2 promoter and MBL‐2 exon 1 genetic variations resulted in decreased protein levels and increased HIV susceptibility. [ 183 ] Polymorphisms in the promoter region are likely to affect gene transcription and disrupt the normal functioning of the gene, resulting in increased disease susceptibility. In addition, polymorphisms in the exon region that code for the protein would have the same effect.…”
Section: Inclusion and Exclusion Criteria For Selected Genes And Snpsmentioning
confidence: 99%
“…MBL‐2 promoter and MBL‐2 exon 1 genetic variations resulted in decreased protein levels and increased HIV susceptibility. [ 183 ] Polymorphisms in the promoter region are likely to affect gene transcription and disrupt the normal functioning of the gene, resulting in increased disease susceptibility. In addition, polymorphisms in the exon region that code for the protein would have the same effect.…”
Section: Inclusion and Exclusion Criteria For Selected Genes And Snpsmentioning
confidence: 99%
“…In search of the effect of MBL-2 polymorphisms on susceptibility and progression of HIV-1 infection in children, Dzwonek et al (2006) observed MBL deficiency more frequently in patients with severe disease. The study suggested that MBL-2 variants may be less frequent in children classified as long-term non-progressors (LTNPs) and hence MBL analysis can be useful in identifying children with slow disease progression and, consequently, may not require immediate antiretroviral treatment (Dzwonek et al 2006). Production of HIV in the presence of the mannosidase I inhibitor deoxymannojirimycin (dMM) significantly enhanced binding of HIV to MBL and increased MBL neutralization of an M-tropic HIV primary isolate.…”
Section: Mbl and Hiv Interactionmentioning
confidence: 99%